Loss of the ClpXP Protease Leads to Decreased Resistance to Cell-Envelope Targeting Antimicrobials in Bacillus anthracis Sterne - Zou, Lang; Evans, Christopher R.; Do, Vuong D.; Losefsky, Quinn P.; Ngo, Diem Q.; McGillivray, Shauna M. (Frontiers in Microbiology, 2021)
The ClpX ATPase is critical for resistance to cell envelope targeting antibiotics in Bacillus anthracis, however, it is unclear whether this is due to its function as an independent chaperone or as part of the ClpXP protease. In this study, we demonstrate that antibiotic resistance is due to formation of the ClpXP protease through construction of a ClpX complementation plasmid that is unable to interact with ClpP. Additionally, we genetically disrupted both clpP genes, clpP1 and clpP2, found in B. anthracis Sterne and find that the loss of either increases susceptibility to cell envelope targeting antimicrobials, although neither has as strong of a phenotype as loss of clpX and neither clpP gene is essential for virulence in a G. mellonella model of infection. Lastly, we looked at changes to cell envelope morphology that could contribute to increased antibiotic sensitivity. We find no difference in cell charge or cell lysis, although we do see increased hydrophobicity in the clpX strain, decreased cellular density and slightly thinner cells walls. We also see significant cell division defects in clpX, although only when cells are grown in the mammalian cell culture medium, RPMI. We conclude that the intrinsic resistance of B. anthracis to cell wall active antimicrobials is dependent on formation of the ClpXP protease and that this could be due, at least in part, to the role of ClpX in regulating cell envelope morphology.